G359(P) An audit of trainee proficiency in the use of the RCPCH early years UK-WHO growth charts. (27th April 2016) - McGlacken-Byrne, SM; McCormack, M
Abstract : Aim: Correctly plotting and interpreting childrens' weight, height, and occipito-frontal circumference (OFC) measurements on a growth chart are key elements of any paediatric examination. We audited trainee proficiency in the use of the RCPCH Early Years UK-WHO growth charts against user guidelines from the Royal College of Paediatrics and Child Health (RCPCH). Methods: We performed a cross-sectional analysis of growth charts in use over a five-day period for inpatients under the age of five in a District General Hospital's neonatal and general paediatric ward. Growth chart type ("0–4" or "Neonatal and Infant Close Monitoring" (NICM)), gender, age, corrected age, and birth gestation were noted. We ascertained if an admission weight, length, and OFC had been plotted, and if these had been plotted correctly. We examined if corresponding centile readings had been recorded, and if these had been correctly interpreted. Results: There was a growth chart in use in 53.3% (n = 32) of the 60 patient records examined, all of which were RCPCH growth charts (75% NICM charts). 93.8% (n = 30) had identified inaccuracies in the plotting or interpreting of measurements. Weight was plotted in 100% (n = 32) of growth charts, and plotted correctly 56.3% of the time (n = 18). OFC was plotted 93.7% of the time (n = 30), and plotted correctly 53.3% of the time (n = 16). Length was plotted in none of the charts reviewed. Weight centile was recorded 56.3% of the time (n = 18), and centiles were interpreted correctly 66.6% of the time (n = 12). OFC centiles were recorded 53.3% of the time (n = 16), and centiles were interpreted correctly 75% of the time (n = 12). Difficulties identified included failure to plot term infants born between 37–42 weeks' gestation on the "0" line at 40 weeks on the NICM charts, and failure to interpret measurements falling within one interquartile space of a centile line as on that centile line. Conclusion: Trainees have difficulty correctly using RCPCH growth charts. These errors, while inconsequential for the majority of patients, could have significant consequences in certain circumstances. Using trainee material available from the RCPCH, we designed educational sessions to improve NCHD proficiency in the accurate use of growth charts. We will re-audit after delivery of these sessions.